Impact of Livestock Grazing on the Floristic Composition: A Case Study of the Mount of Tessala, Western Algeria - Kouider, Cherifi; Mehdadi, Zoheir; Latreche, Ali; Hazem, Zouaoui; El Zerey, Wael (International Journal of Environment, 2014)
The present work focuses on evaluating the impact of livestock grazing on the floristic composition in the mount of Tessala (Western Algeria). Phytoecological surveys were carried out at seven stations around north and south slopes of the mount. The obtained results through Principal Components Analysis (PCA) indicated the impact of man and herd on the floristic composition of sampling stations. Indeed, stations where grazing is low, have greater species richness marked by the strong presence of palatable species, unlike stations under permanent grazing, characterized in particular by the appearance of non-palatable species. Moreover, we note the dominance of therophytes at all stations not only due to grazing pressures but also to drought in the study area. DOI: http://dx.doi.org/10.3126/ije.v3i3.11078 International Journal of Environment Vol.3(3) 2014: 186-200